Prevalence of nosocomial pneumonia in critically ill patients receiving omeprazole therapy (Research, Society and Development, 2025)
Proton Pump Inhibitors (PPIs) are drugs used for the prophylaxis of stress ulcers, as well as in other clinical situations that require reduction of gastric hydrochloric acid production. However, evidence suggests that PPIs may increase the risk of pneumonia due to consequent alterations in gastrointestinal microbiota and immune response. Objective: To analyze the association between the use of 40 mg injectable omeprazole and the occurrence of pneumonia. Methodology: Analysis of 48 medical records of patients treated with 40 mg intravenous omeprazole in the Intensive Care Unit of a teaching hospital during 2023 and 2024. Results: Eight cases of pneumonia were identified, predominantly in men aged 51 to 60 years, a group in which four deaths also occurred. Conclusion: Although omeprazole may increase the risk of pneumonia by reducing gastric acidity and favoring bacterial colonization, the study highlights that pneumonia in ICUs is a multifactorial event. Thus, it is concluded that the benefit of omeprazole use outweighs the risks, especially when combined with good clinical practices and individualized monitoring.